Parcs publics et paysagisme au Japon entre le milieu du xixe siècle et le début du xxe siècle - Yoko Mizuma (Projets de Paysage)
The opening up of the country at the time of the Meiji revolution in 1686 was a time of great change in the history of gardens in Japan. At that time the model of the Japanese garden became more diverse under Western influence. This evolution was heightened and accelerated by a new urban component, introduced from outside, that of the “public park”. It is around the concepts of the “public park” and “of the Westernisation of the garden style” that the Japanese school of landscape architecture imagined and designed a new type of park. Two schools inspired by two different European countries, played a key role : one, the Seiroku Honda school (1866-1952), founded on silviculture, inspired by the German school, and the other, the Hayato Fukuba school (1856-1921), founded on ornamental horticulture, influenced by the French school. Through the history of the development of the concept of the public park and the examples of three parks and gardens created at the beginning of the 20th century, it is possible to understand how these two schools stimulated the development of a new form of landscape architecture in Japan.